Capturing Morphophonemic Processes in the Short Movie Entitled “Fool’s Day” - Rahardi, Panggih (International Journal of English Education and Linguistics (IJoEEL), 2023)
A movie is a form of literature that contains linguistic features in its script. The script of a movie uttered by the actors has many interesting linguistic aspects that can be studied. Hence, this study aims to identify the morphophonemic processes in the movie "Fool's Day". The data of this study was obtained from the movie script, and a descriptive qualitative method was employed to analyze it. This study showed that morphophonemic processes frequently occurred in the script and involved the more basic processes. The findings indicate four types of the morphophonemic process throughout the movie script: schwa, voicing assimilation, vowel lengthening, and vowel changing. It was found that vowel changing processes are most frequent in the movie "Fool's Day" script